Permukiman Tepi Sungai Ilegal: Dampak Kondisi Sosial-Ekonomi, Ketidakstabilan Ekonomi, Ketidakadilan Spasial Perkotaan dan Kebijakan Pemerintah - Kusumawardani, Yuliarti Nurul; Soesanta, Prabawa Eka; Hamzah, A. Hadian Pratama (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to describe the influence of socio-economic conditions, economic instability, urban spatial injustice, and government policies on the development of illegal settlements on the river border of Bima City. The research is quantitative research that is associative. The respondents of this study are 56 members or heads of families who live on the banks of the river in Bima City. The instruments of this research are questionnaires and documentation. Data analysis was carried out using multiple regression analysis. The results of the study show that socio-economic conditions, economic instability, spatial planning justice, and government policies have a significant effect on illegal settlement on the river border of Bima City. As a strategy for structuring illegal settlement areas on the border of the river in Bima City, it is important to pay attention to welfare, urban spatial planning, and commitment to law enforcement by the government. Illegal riverside settlements are a common phenomenon in urban areas, especially in regions with rapid population growth. This study aims to analyze the impact of social and economic conditions, economic instability, and urban spatial injustice on illegal riverside settlements, as well as evaluate government policies in addressing this issue. The results show that illegal riverside settlements have a negative impact on the socio-economic condition of residents, increase economic instability, and exacerbate urban spatial injustice. Therefore, the government needs to develop more effective policies to address the issue of illegal riverside settlements and improve the quality of life for residents.